Analysis of Classroom Light Intensity as an Indicator of Effects of Eyestrain in the Effectiveness of the Learning Process at the Universitas Muhammadiyah Lamongan (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2023)
Eye fatigue may be brought on by the room's inappropriate lighting level. Classroom lighting is one of the physical aspects of learning that can impact how well students learn. The University of Muhammadiyah Lamongan has never reviewed the amount of light present in classrooms, nevertheless. Therefore, in this study, we brought up the issue of the connection between the classroom's light intensity and the measure of the impact of eye tiredness on the efficacy of learning at Universitas Muhammadiyah Lamongan. Based on a review of the outcomes of mapping light intensity in classrooms at the Universitas Muhammadiyah Lamongan, this study intends to ascertain the impact of room light intensity on eye fatigue in students as well as review classroom facilities. Analytical observation is the research methodology used. The information was gathered using a questionnaire about using a lux meter to measure light intensity and creating two- and three-dimensional contour maps of the distribution of light intensity in classrooms. Following the collection of data from the two processes, the data was examined to determine whether the respondent survey results and the light intensity contour map data could be correlated based on the respondent's seat in the classroom. Students that were enrolled in classes at Universitas Muhammadiyah Lamongan were the respondents. According to the study's findings, eye fatigue affects students in class A302 at Universitas Muhammadiyah Lamongan because of the room's low light intensity values, which range from 56.5 to 67.6 Lux.  If the light intensity value is greater than 69 lux and is evenly distributed among all coordinate locations, which are the points where students are seated during lecture activities in class A302, the weary eye effect will vanish.